Anti-ulcer activity of green synthesized selenium nanoparticles using Nigella sativa L. seed extract in rats - Elwej, Awatef; Al-Otaibi, Fawziah; Boukholda, Khadija; Alminderej, Fahad; Alotaibi, Faez; Kaabi, Amani; Ali, Nada M.; Fetoui, Hamadi; Aouadi, Kaiss; Kadri, Adel (Frontiers in Pharmacology, 2025)
Background/ObjectivesSelenium nanoparticles (SeNPs) have gained importance due to their potential biological properties. The present work is the first study to investigate the protective effect of selenium nanoparticles (SeNPs) synthesized using Nigella sativa L. seed extract on stomach ulcers in adult rats.MethodsThe formation of SeNPs was confirmed by Ultraviolet–visible (UV), Fourier Transform Infrared Spectroscopy (IR), Thermal-gravimetric analysis (TGA-DTA coupled system), X-ray diffraction analysis (XRD) and scanning electron microscope (SEM) analysis. Animals were classified into 4 distinct groups. Group 1, serving as controls; group 2, serving as ulcer-group where rats received a single oral dosage of 96% ethanol (5 mL/Kg BW). Rats in Group 3 were given orally 0.5 mg/kg BW of SeNPs 1 hour before ethanol-induced gastric ulcer. Group 4 received SeNPs only (0.5 mg/kg BW) by intragastric way and served as a positive control.ResultsGreen synthesis was confirmed via UV-Vis spectroscopy (230 nm peak), FTIR revealed functional groups (O–H, C=O, Se–O or Se–Se). XRD pattern shows an average crystallite sizes of nanoparticles were around 26 (4) and 268 (4) nm for β-SeO2 and g-SeO2 forms, respectively. SEM examination indicated that SeNPs have a predominantly spherical to sub-spherical morphology. TG-DTA analysis demonstrates the good thermal stability of selenium nanoparticles, evidenced by initial moisture loss, controlled degradation of organic stabilizers and the formation of a stable inorganic selenium core. SeNPs’ protective effects were assessed by evaluating the ulcer index, conducting histological analysis, measuring oxidative stress markers and antioxidant defenses, as well as examining key factors involved in gastric mucosal protection. Our results demonstrated that SeNPs reduced malondialdehyde (MDA), and advanced oxidation protein product (AOPP) levels, nitric oxide (NO) levels in stomach of ethanol-induced gastric ulcer, as well as the activities of Catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD); while glutathione (GSH) and non-protein thiols (NPSH) levels were restored reaching control values. Moreover, the gastric healing effect of SeNPs pretreatment was associated with an improvement in hematological parameters and a reduction in CRP levels.ConclusionThese findings underscore the potential of SeNPs to enhance the antioxidant defense system of gastric mucosal cells and prevent ethanol-induced gastric damage in rats.